Implementation of Learning Strategies for SD Muhammadiyah 1 Krian During the Covid 19 Pandemic - Berliana Khofifah Febriyanti; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The Covid-19 pandemic that entered Indonesia since March 2020 had a tremendous impact in all aspects, including education. From those who use face-to-face strategies, they must now change to online learning strategies. The purpose of this study was to find out the learning strategies used at SD Muhammadiyah 1 Krian during the Covid-19 pandemic and find the right solution to the existing problems. This study uses descriptive qualitative research methods. Data collection techniques in this study through interviews, documentation and observation. The results and discussion are the learning strategies used by SD Muhammadiyah 1 Krian during the Covid-19 pandemic are to use LMS Sakri, Zoom Meeting, WhatsApp, and Microsoft 365 with an intensity of 5 effective days, 3 days face-to-face remotely via zoom, 2 days offline. in the form of sending learning videos and assignments. However, the learning strategy of SD Muhammadiyah 1 Krian during online learning during the Covid-19 pandemic also encountered obstacles including, teachers needed adjustments because they were required to learn IT and be creative, it took a long time to prepare learning media in the form of shooting videos, making learning videos, making assignments. portfolio, and other assignments. The solution that can be done is to prepare a large internet connection, provide IT training to teachers because online learning requires creativity and innovation from the teacher, so that the transfer of knowledge and skills can run optimally